EARLY‐LIFE PREDICTORS OF INTERNALIZING SYMPTOM TRAJECTORIES IN CANADIAN CHILDREN. Issue 7 (14th January 2014) - Weeks, Murray; Cairney, John; Wild, T. Cameron; Ploubidis, George B.; Naicker, Kiyuri; Colman, Ian
<x xml:space="preserve">Abstract</x> Background Previous research examining the development of anxious and depressive symptoms (i.e., internalizing symptoms) from childhood to adolescence has often assumed that trajectories of these symptoms do not vary across individuals. The purpose of this study was to identify distinct trajectories of internalizing symptoms from childhood to adolescence, and to identify risk factors for membership in these trajectory groups. In particular, we sought to identify risk factors associated with early appearing (i.e., child onset) symptoms versus symptoms that increase in adolescence (i.e., adolescent onset). Method Drawing on longitudinal data from the National Longitudinal Survey of Children and Youth, latent class growth modeling (LCGM) was used to identify distinct trajectories of internalizing symptoms for 6, 337 individuals, from age 4–5 to 14–15. Multinomial regression was used to examine potential early‐life risk factors for membership in a particular trajectory group. Results Five trajectories were identified as follows: "low stable" (68%; reference group), "adolescent onset" (10%), "moderate stable" (12%), "high childhood" (6%), and "high stable" (4%). Membership in the "adolescent onset" group was predicted by child gender (greater odds for girls), stressful life events, hostile parenting, aggression, and hyperactivity. Membership in the "high stable" and "high childhood" trajectory groups (i.e., child‐onset) was additionally predicted by maternal depression, family dysfunction, and difficult temperament. Also, several significant gender interactions were observed. Conclusions Causal mechanisms for child and adolescent depression and anxiety may differ according to time of onset, as well as child gender. Some early factors may put girls at greater risk for internalizing problems than boys.